The Low Value of Equality and Social Inclusion in Fragmented and Discriminatory Latin American Societies : Pensions and Health - Gomes, Cristina (Advances in Social Sciences Research Journal, 2019)
This article aims to analyze the fragmented mix of social policies in Latin America, guided by minimalist principles and instruments of liberal thinking on individual meritocracy and contributory insurance, in order to discuss the challenges to and possibilities of developing universal policies. The article describes the historically social, economic and political contexts and pressures that frame the process of building fragmented social policies in the region; the contradictions, disadvantages, and limited achievements of these fragmented systems in terms of coverage, generosity and quality of health and pensions. Results show that expansive and fragmented welfare policies reproduce differences in quality and scope and increase social inequalities and conflicts; the challenges of building universal rights, citizenship and equality in Latin America, considering current public-private agreements, political coalitions, and interclass alliances, and the need to reorient social policies in order to overcome conflicts of interest, discrimination and market resistance, and to promote equality.